DAMPAK ALIH FUNGSI LAHAN PERTANIAN TERHADAP PRODUKSI PERTANIAN TANAMAN PANGAN DI KABUPATEN BOYOLALI - Joko Sutrisno (Universitas Sebelas Maret, 2007)
The aims of this study to know the impact of agricultural land use changes to non agricultural land use, for agriculture production especially food crop production in the area. The study is descriptive research in Kabupaten Boyolali Central of Java. Because that is many agricultural land use changes to residential, industrial and public facility land